Innovating governance: Building resilience against COVID-19 pandemic and other risks - Aubrey D. Tabuga; Sonny N. Domingo; Charlotte Justine Diokno-Sicat; Valerie Gilbert T. Ulep (Philippine Institute for Development Studies (PIDS), 2020)
The unprecedented coronavirus disease (COVID-19) pandemic is the most challenging public health crisis the world has faced in a century. It has overwhelmed global and national health service and disaster management infrastructure and brought economies to a standstill/halt. It serves as both an eye-opener and an impetus to leapfrog reforms to strengthen governance systems and structures. It propels us to innovate and install more forward-looking systems and strategies that will enable us to permanently gain the capacity to survive and win over multiple and complex challenges that we face now and in the future. In the public sector, the pandemic shows the importance of having harmonization and synergy between and among national government agencies and sub-national governments. It has illustrated the importance of investing in digital education, e-commerce, and innovative ways of delivering social protection as well as fostering business innovations to meet fast-changing demand. The literature discusses quite a number of public sector innovations particularly in developed countries and the approaches are combinations of various governance methods, with styles varying depending on the context. Yet on the overall, the public sector has very few models for innovation. This background paper briefly scans the recent literature of public sector innovations and other efforts implemented in the strengthening of governance systems. The goal is to gather insights that may be useful for the Philippines case for enhancing its governance strategies, improving overall performance in service delivery, and building resilience against risks in the long-term.
Keywords: 330; COVID-19; disaster management; risk reduction; innovative governance; public sector innovation